Maintenance management at Coastal Resort / Noor Husnaini Isa - Isa, Noor Husnaini (Faculty of Architecture, Planning and Surveying, 2008)
A resort is a place used for relaxation or recreation, attracting visitors for holidays or vacations. Means any hotel, resort complex, apartment building, condominium, condo hotel, townhouse or the like, in which the Club Plan may be operated from time to time and may either be a Club Resort or an Affiliate Resort. Location where all services and entertainment is under one roof. They can vary from luxury to budget/economy. Usually all is included under one-price umbrella. Resort be effective if have the proper maintenance management. The Improper supervision has lead to poor performance which was due to lack of explicit property objectives. This study focused on identifying to find out the maintenance management at coastal resort, to understand the important of resort maintenance management, how they control the maintenance is built from timber and to suggest recommendation the best maintenance and management for resort maintenance management. The process includes producing a new vision statement, revising mission statement, identifying goals and objectives. In order to achieve the objectives identified, literature review was done, then the data was collected using questionnaires, the collected data was analyzed using relative index analysis. Findings had shown that although many resorts have their own maintenance management system but the condition of resort still at average level which means performance fall shorts of requirement expectation and need improvement due to improper maintenance practice. Hence, to improve the current maintenance management system for resort, strategic planning has been suggested in order to increase performance, to provide an effective maintenance management, provide control for maintenance activities, improve quality, cost effective satisfaction, and to optimize the maintenance processes for their resort.